The people vs. democracy : why our freedom is in danger and how to save it - Mounk, Yascha (London Harvard University Press, 2018)
From India to Turkey, from Poland to the United States, authoritarian populists have seized power. Two core components of liberal democracy--individual rights and the popular will--are at war, putting democracy itself at risk. In plain language, Yascha Mounk describes how we got here, where we need to go, and why there is little time left to waste.--
Introduction: Losing our illusions -- Part 1. The crisis of liberal democracy: Democracy without rights -- Rights without democracy -- Democracy is deconsolidating -- Part 2. Origins: Social media -- Economic stagnation -- Identity -- Part 3. Remedies: Domesticating nationalism -- Fixing the economy -- Renewing civic faith -- Conclusion: Fighting for our convictions.
Includes bibliographical references (pages [269]-357) and index.
Keywords: Democracy; Populism; Authoritarianism; Human rights; Political participation